The union between the kingdoms of England and Scotland in 1707 - Al-Tamimi, Maria Hassan Moghtaz (Al-Adab Journal, 2022)
The question of the unification of the English and Scottish crowns has occupied the minds of the Kings of England since 1603 and the formation of a central political structure, The first weak attempts began with an exchange of ideas between King James I and politicians from England and Scotland, But the difficulties were great for that union, because both kingdoms intersected in all political, legal, economic and cultural aspects. The union attempt was renewed during the reign of King William III as well, but Scotland’s loss in the Darien project had caused an economic crisis for it and thus worsened the relations between the two kingdoms after That Scotland demanded compensation for its loss from England and set up a company of their own, All of these things made it difficult to achieve union, And as soon as the Queen assumed the throne of England, she set her sights on uniting the two kingdoms in order to prevent Scotland from slipping into the hands of her enemies from the conspirators in France, and to ensure the security and safety of the two kingdoms.